Mortality of air-layered plants of litchi (Litchi chinensis) and histopathology of affected roots in Bihar, India - KUMAR, VINOD; KUMAR, AMRENDRA; ANAL, AJIT KUMAR DUBEDI (The Indian Journal of Agricultural Sciences, 2019)
Mortality of layers after severing them from the mother plants and establishment in the nursery on their own root systems is a major constraint in producing large number of quality planting material. Studies were conducted to know the extent and aetiology of mortality of air-layered plants after its planting in polybags, and examined histopathology of affected versus healthy roots of these plants. The results showed that the maximum mortality of plants was around 60 DAP in polybags, the mean mortality being in the range of 10.3 to 26.7%. After 60 DAP, the inflated (puffy) roots failed to support growth of plants. Mortality of the plants occurred because there was no development of fibrous root system, coupled with possibly exhaustion of reserve nutrients in air-layered plants. Thus, it was conclusively proved that mortality of air-layers in initial stage was a growth related problem rather than of a pathogenic aetiology. Further physiological study of growth and establishment of air-layers after planting may be examined to have more insight into the problem that may improve survival rate of air-layers in nurseries.